Experimental investigation on the corrosion detectability of a36 low carbon steel by the method of phased array corrosion mapping - Tai, Jan Lean; Grzejda, Rafał; Sultan, Mohamed Thariq Hameed; Łukaszewicz, Andrzej; Shahar, Farah Syazwani; Tarasiuk, Wojciech; Rychlik, Arkadiusz (MDPI, 2023)
Petrochemical plants use on-stream inspection often to detect and monitor the corrosion on the equipment and piping system. Compared to ultrasonic thickness gauging and pulse-echo A-scan, phased array corrosion mapping has better coverability and can scan a large area to detect general and localized corrosion. This paper’s objective is to obtain documentary evidence for the accuracy of corrosion detection from 30 °C to 250 °C on A36 low-carbon steel by carrying out simulation experiments every 10 °C step. A minimum of three sets of phased array corrosion mapping data in each temperature were collected to study and evaluate the detectability. The data evidence could enhance the confidence level of the plant’s end users in using phased array mapping in the future during inspections. The experiments were found to be insufficiently thorough despite addressing the initial concerns, leaving more area for discussion in further studies, such as expanding the investigation to thicker carbon steel, stainless steel, and wedge materials.